Reflections on the regulatory field covering the development of paediatric medicinal products: a brief overview of current status and challenges - Lehmann, Birka (Frontiers in Pharmacology, 2024)
Many medicinal products are initially developed and tested in adults, and often, only a limited amount of data on their safety and efficacy in children exist. Consequently, paediatric healthcare providers sometimes need to make informed decisions about using medicinal products in children based on available fragmentary data. Ethical guidelines emphasise the importance of protecting children and ensuring they receive safe and effective medical treatments. Paediatric clinical trials should be conducted to provide evidence-based care with specific attention to minimise risks to children. This highlights the dilemma of finding a balance between protecting children and adolescents (and avoiding unnecessary clinical trials) and obtaining reliable, robust and justified data to treat them adequately and not in an off-label manner with unknown risks. For years, paediatricians maintained that children and adolescents are not treated based on up-to-date scientific knowledge and justification. The slogan “children are not small adults” summarised the concerns in a catch phrase. Different stakeholders have taken a variety of actions to address this concern.